Team Programming in Golog under Partial Observability - Farinelli, A; Finzi, A; Lukasiewicz, T (2007)
In this paper, we present the agent programming language TeamGolog, which is a novel approach to programming a team of cooperative agents under partial observability. Every agent is associated with a partial control program in Golog, which is completed by the TeamGolog interpreter in an optimal way by assuming a decision-theoretic semantics. The approach is based on the key concepts of a synchronization state and a communication state, which allow the agents to passively resp. actively coordinate their behavior, while keeping their belief states, observations, and activities invisible to the other agents. We show the usefulness of the approach in a rescue simulated domain.